2012
DOI: 10.1016/j.ijrobp.2012.07.1285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reduced-volume Intensity Modulated Radiation Therapy on Disease Control for Nasopharyngeal Carcinoma

Abstract: ObjectiveTo investigate the feasibility of using intensity-modulated radiotherapy (IMRT) with reduced, high-dose target volumes for nasopharyngeal carcinoma (NPC). MethodsThe first 57 patients (admitted from October 2005 to May 2008) were treated with large-target-volume IMRT (LV-IMRT). For the LV-IMRT group, the CTV at 70 Gy (CTV70) was delineated as the gross target volume (GTV) plus 7mm, with or without the first-echelon lymphnode region. The next 56 patients (admitted from June 2008 to November 2011) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…2) to minimize unnecessary radiation doses to normal tissue without interfering with the treatment outcomes. 12 This finding further confirmed the feasibility of IMRT with reduced CTV for the lateralized tumours of NPC patients. They found that no patients suffered recurrence after a median follow-up time of 33 months.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2) to minimize unnecessary radiation doses to normal tissue without interfering with the treatment outcomes. 12 This finding further confirmed the feasibility of IMRT with reduced CTV for the lateralized tumours of NPC patients. They found that no patients suffered recurrence after a median follow-up time of 33 months.…”
Section: Discussionsupporting
confidence: 69%
“…This finding can be verified by the excellent local control achieved in NPC patients treated with reduced CTV of IMRT compared with the IMRT plans per the current guidelines, and marginal or outside-field failure was uncommon with reduced 12,21 Some oncologists even suggested that the margin expansion from the GTV to the CTV could be omitted, 22 considering the rapid development of technologies in both diagnostic imaging and radiation therapy over the past decades which have improved the accuracy of gross tumour delineation and targeting. In this study, we used biopsy of several sites of the nasopharynx and found that most patients with clinically diagnosed unilateral cancer of the nasopharynx can be confirmed by pathological biopsy.…”
Section: Discussionmentioning
confidence: 67%
“…The initial primary radiation therapy plan was generated as previously described [11]. In short, the planning target volume (PTV) was extended 0 to 3 mm from the clinical target volume (CTV).…”
Section: Initial Primary Radiation Therapy and The Salvage Sbrt Treatmentioning
confidence: 99%
“…Radiation therapy with or without concurrent chemotherapy represents the standard treatment for nasopharyngeal cancer (NPC) and leads to a 5-year local control rate of greater than 85% [1][2][3][4][5][6][7][8][9]. However, local recurrence still represents a major source of morbidity and mortality in patients with advanced stage NPC [10,11]. Because of the invasive nature of the malignancy which may involve many critical tissues at skull base, radiation therapy often remains to be the main salvage treatment modality once the disease recurs locally.…”
Section: Introductionmentioning
confidence: 99%
“…Size of the PTV can be a crude predictor of acute RT toxicity. 31, 32 However, we found that patients with larger PTV actually had smaller setup errors in the SI and AP directions. Our image guidance procedure allows the observers to apply additional shifts to ensure adequate target coverage following automatic correction of setup displacements.…”
Section: Discussionmentioning
confidence: 59%